Effects of Tin and Sulfur Chemical Substitution on the Structural and Electrical Properties of Cucr2se4 Selenospinel - Aravena-Ponce, D; Aravena-Ponce, D (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
A series of CuCr2‐xSnxS2.3Se1.7 and CuCr2‐xSnxS1.7Se2.3 (x = 0.4, 0.6, and 1.0) compounds were prepared by solid‐state reaction at a high temperature. Single‐crystal X‐ray diffraction analysis showed that CuCr1.1Sn0.9S2.3Se1.7 crystallizes in a spinel‐type structure (cubic Fd3m space group). The others samples were also consistent with a spinel‐type structure but through powder X‐ray diffraction patterns and Rietveld refinements. The systems studies showed p‐type semiconductor behavior with a carrier concentration per volume of approximately ~+1020 cm−3. The electrical conductivity, σ, showed tin‐content dependence. The conductivity of CuCr2‐xSnxS1.7Se2.3 increased from ~9.0 to ~17.0 S∙cm−1 at room temperature (RT) for x = 0.4 and 0.6, respectively, and the magneto‐resistance average value determined for CuCr2‐xSnxS2.3Se1.7 and CuCr2‐xSnxS1.7Se2.3 was approximately ~10−4 Ω (0.566 T, external magnetic field). DFT calculations revealed that the Cr centers concentrated most of the spin density. A smaller spin polarization featuring the opposite spin was observed for S/Se atoms. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.